Positive selective sweeps of epigenetic mutations regulating specialized metabolites in plants - Shirai, Kazumasa; Sato, Mitsuhiko P.; Nishi, Ranko; Seki, Masahide; Suzuki, Yutaka; Hanada, Kousuke (Genome Research, 2021)
DNA methylation is an important factor regulating gene expression in organisms. However, whether DNA methylation plays a key role in adaptive evolution is unknown. Here, we show evidence of naturally selected DNA methylation in Arabidopsis thaliana. In comparison with single nucleotide polymorphisms, three types of methylation—methylated CGs (mCGs), mCHGs, and mCHHs—contributed highly to variable gene expression levels among an A. thaliana population. Such variably expressed genes largely affect a large variation of specialized metabolic quantities. Among the three types of methylations, only mCGs located in promoter regions of genes associated with specialized metabolites show a selective sweep signature in the A. thaliana population. Thus, naturally selected mCGs appear to be key mutations that cause the expressional diversity associated with specialized metabolites during plant evolution.